`Football as opportunity!` the potential of inter- and transdisciplinary research to explore and transform gender inequalities: a special focus on qualitative linguistic discourse analysis - Graf, E.-M.; Fleischhacker, M. (Soccer & Society, 2023)
Football is of global socio-cultural and economic significance. Though it has changed considerably regarding the participation and representation of women, it is (still) built on condensed traits of hegemonic masculinity, gendered norms, and expectations. At the same time, football entails great emancipatory and empowering opportunities and thus offers itself as an empirical laboratory for gender research and as a blueprint for sustainable transformation in other (similarly) gendered societal domains. This contribution shows how existing gender inequalities in (Austrian) female football might be explored and transformed by means of inter- and transdisciplinary research. It details the scope, goals, and research design of such a project in the context of GOAL (Gender [In]Equality in Football: Developing Opportunities through Assessment and Leadership Transformation), an envisioned, prospective cooperation between linguistics, anthropology, sports pedagogy, and economic sciences with various practice partners. A special focus will be on the role and potentials of qualitative linguistic discourse analysis in exploring causes and characteristics of gender inequality in (female) football as experienced, practiced, represented, and reproduced, but also challenged by social actors on and off the field. First findings from the related, (purely) linguistic research project More than a Game will be utilized to further illustrate this point.